2008
DOI: 10.1111/j.1747-4477.2007.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supraperiosteal injection of dexamethasone on postoperative pain

Abstract: Many patients suffer from mild, moderate or severe pain during or after root canal therapy. The purpose of this study was to evaluate the efficacy of supraperiosteal injection of dexamethasone into the periapical tissues to prevent postoperative pain associated with inflammation. In a double-blind, placebo-controlled clinical trial, 100 patients with moderate or severe pain who were referred to dental school of Tehran Islamic Azad University participated in this study. All patients had a tooth with clinical di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 10 publications
3
63
0
1
Order By: Relevance
“…Findings of this study is quite similar to the previous studies using submucosal route. VAS Score and total number of analgesics used was not statistically different between the groups [12][13][14][15]. However, Majid [16] found that the significant analgesic effect could be a different mechanism which was not clearly explained.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Findings of this study is quite similar to the previous studies using submucosal route. VAS Score and total number of analgesics used was not statistically different between the groups [12][13][14][15]. However, Majid [16] found that the significant analgesic effect could be a different mechanism which was not clearly explained.…”
Section: Discussionmentioning
confidence: 96%
“…Many reports support the use of local application of dexamethasone in the setting of TMS [11][12][13][14][15][16]. But those studies demonstrated conflicting results because of the limited number of subjects, different route and dose of corticosteroid administered, use of different surgical techniques and lack of standardized anaesthetic technique (Local or General).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review showed that between 3% and 58% of patients were reported to have experienced endodontic postoperative pain (5). The management of postoperative pain has been the subject of many research studies, including preoperative explanations and instructions (6), long-acting anesthesia (7), the glide path (8), occlusal reduction (9, 10), medication using salicylic acid (11), non-steroid anti-inflammatory drugs (NSAIDs) (12), combination of ibuprofen and acetaminophen (13), narcotic analgesics (14), a combination of narcotic analgesics with aspirin (15) or acetaminophen (16), and steroidal anti-inflammatory drugs (17,18).…”
Section: Introductionmentioning
confidence: 99%